International political theory and the refugee problem - Saunders, Natasha (Routledge research on the global politics of migration, 2018)
The refugee problem' is a term that it has become almost impossible to escape. Cases of refugee protest in Europe, and the burgeoning Sanctuary Movement in the UK, are examined as two sub-state and popular movements which could constitute such creative solutions to a reframed problem.